2012
DOI: 10.1098/rspb.2012.1651
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and process of biotic homogenization in the New Pangaea

Abstract: Human activities have reorganized the earth's biota resulting in spatially disparate locales becoming more or less similar in species composition over time through the processes of biotic homogenization and biotic differentiation, respectively. Despite mounting evidence suggesting that this process may be widespread in both aquatic and terrestrial systems, past studies have predominantly focused on single taxonomic groups at a single spatial scale. Furthermore, change in pairwise similarity is itself dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
175
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(190 citation statements)
references
References 34 publications
12
175
2
1
Order By: Relevance
“…Many previous studies of biotic homogenisation have analysed changes over time (e.g. Olden and Rooney 2006;Lôbo et al 2011); however, data on spatially distinct communities are much more widely available than temporal data (McKinney 2006) and have increasingly been used to quantify homogenization (Baiser et al 2012;de Solar et al 2015). If anything, spatial comparisons are likely to underestimate the effects of land conversion on biodiversity (França et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies of biotic homogenisation have analysed changes over time (e.g. Olden and Rooney 2006;Lôbo et al 2011); however, data on spatially distinct communities are much more widely available than temporal data (McKinney 2006) and have increasingly been used to quantify homogenization (Baiser et al 2012;de Solar et al 2015). If anything, spatial comparisons are likely to underestimate the effects of land conversion on biodiversity (França et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, TD has been the dominant process within biotic units, and many non-native taxa with narrow geographic distributions might be the cause for this process. Parallel assessments in regions with similar climates have been crucial to improve our understanding of drivers of biological invasions (e.g., plants: Pauchard et al 2004;fishes: Marr et al 2010fishes: Marr et al , 2013; but see Baiser et al 2012 world, including central Chile (32°S-40°S); they found that TH was prevalent with a ΔCS av = 8.4 %, and this is higher than our estimate for comparisons involving watersheds in Central (U3) and South-Central (U4) (ΔCS av = 2.9 %). Clearly, scale (level of resolution or grain and geographic coverage) has an impact on assessments of TH as well as differential species richness and turnover (see McKinney 2004;Olden, 2006;Baiser et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Parallel assessments in regions with similar climates have been crucial to improve our understanding of drivers of biological invasions (e.g., plants: Pauchard et al 2004;fishes: Marr et al 2010fishes: Marr et al , 2013; but see Baiser et al 2012 world, including central Chile (32°S-40°S); they found that TH was prevalent with a ΔCS av = 8.4 %, and this is higher than our estimate for comparisons involving watersheds in Central (U3) and South-Central (U4) (ΔCS av = 2.9 %). Clearly, scale (level of resolution or grain and geographic coverage) has an impact on assessments of TH as well as differential species richness and turnover (see McKinney 2004;Olden, 2006;Baiser et al 2012). Because we document no local extinctions, species turnover seems less likely to have a significant impact, suggesting a difference in the level of resolution might be the best explanation for differences between Marr et al (2010) and this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting genetic, taxonomic and functional impoverishment is viewed as a major threat to biodiversity (Olden et al 2004;Mouillot et al 2013). Biotic homogenization has been demonstrated to occur across nearly all taxonomic groups, spatial scales and grain sizes (Baiser et al 2012). This makes it paramount to understand how biotic homogenization can be counteracted at each of these scales.…”
mentioning
confidence: 99%